The Influence of Training, Leadership Style, and Work Discipline on the Performance of Employees in the Accounting Divisionand Finance at the Indonesian Post Office Surabaya Main Branch - Arraya Akhsa Putra Priyadizah; Bowo Santoso (Digital Innovation : International Journal of Management, 2025)
Nowadays, the success of a company in achieving its goals certainly cannot be separated from employee performance. From this, companies should be able to understand the importance of Human Resources (HR) in the company because they all work together to achieve the goals the company wants to achieve. On this basis, this research aims to determine the influence of training, laissez-faire leadership style, and work discipline on employee performance in the Accounting and Finance Division at the Surabaya Main Branch of the Indonesian Post Office. This research uses quantitative methods. The population is all employees at the Surabaya Main Branch Post Office in the Accounting and Finance division, totaling 55 people. Sampling is saturated sampling by making the entire population as respondents. The scale used in this research is an ordinal scale with the Likert method. Data collection techniques are interviews and questionnaires by distributing statements directly to respondents. Then for data analysis techniques using Partial Least Square (PLS) measurements of the outer model and inner model. The research results show that training, laissez-faire leadership style, and work discipline support increased employee performance. This shows that the better and more effective the training, laissez-faire leadership style, and work discipline implemented, the better the employee performance at the Surabaya Main Branch Post Office will be.